2021
DOI: 10.3390/foods10123052
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Diet as a Strategy for Weight Control

Abstract: According to the World Health Organization, obesity has nearly tripled since the 1970s. Obesity and overweight are major risk factors for cardiovascular diseases, diabetes, inflammatory-mediated diseases, and other serious medical conditions. Moreover, recent data suggest that obesity, overweight, diabetes, and cardiovascular diseases are risk factors for COVID-19-related mortality. Different strategies for weight control have been introduced over the last two decades. Unfortunately, these strategies have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 82 publications
(330 reference statements)
2
30
0
1
Order By: Relevance
“…Interestingly, a study demonstrated that, despite the calcium level dropping at 3 weeks, it appears to rise after 6 weeks of adhering to a healthy PBD ( 33 ). Vegan diets have been linked to better gut microbiota symbiosis, enhanced insulin sensitivity, peroxisome proliferator-activated receptors (PPARs) stimulation, and upregulation of mitochondrial uncoupling proteins ( 19 ).…”
Section: What Are Pbds?mentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, a study demonstrated that, despite the calcium level dropping at 3 weeks, it appears to rise after 6 weeks of adhering to a healthy PBD ( 33 ). Vegan diets have been linked to better gut microbiota symbiosis, enhanced insulin sensitivity, peroxisome proliferator-activated receptors (PPARs) stimulation, and upregulation of mitochondrial uncoupling proteins ( 19 ).…”
Section: What Are Pbds?mentioning
confidence: 99%
“…In the literature, there are several theories about why PBD is suitable for weight loss. The most widely accepted theory is that plants have low-calorie density (the number of kilocalories (kcal) per unit weight of food) and reduced fat content ( 19 ). Low-calorie-dense foods are more beneficial for weight loss than smaller portion sizes ( 19 ).…”
Section: What Are Pbds?mentioning
confidence: 99%
See 3 more Smart Citations